Circulating autoantibodies, acute phase reactants, and cytokines in relation to HLA genotype and disease activity in rheumatoid arthritis - Anderson, Ronald (University of Pretoria, 2013)
Thesis (PhD (Immunology))--University of Pretoria, 2011.